Lifestyle Modification Program on a Metabolically Healthy Elderly Population with Overweight/Obesity, Young-Old vs. Old-Old. CONSEQUENCES of COVID-19 Lockdown in This Program - Lidia Cobos-Palacios (MDPI AG, 2021)
The SARS-CoV-2 pandemic led to lockdowns, which affected the elderly, a high-risk group. Lockdown may lead to weight gain due to increased food intake and reduced physical activity (PA). Our study aimed to analyze the impact of a 12-month lifestyle intervention on a metabolically healthy overweight/obese elderly (MHOe) population and how the lockdown by COVID-19 affected this program. Methods: MHOe participants (65–87 years) were recruited to participate in a lifestyle modification intervention based on the Mediterranean diet (MedDiet) and regular PA. Participants were classified into two groups: young-old (<75 years) or old-old (≥75 years). Anthropometric and clinical characteristics, energy intake, and energy expenditure were analyzed at baseline and after 12 months of intervention. Results: The final sample included 158 MHOe participants of both sexes (age: 72.21 ± 5.04 years, BMI: 31.56 ± 3.82 kg/m2): 109 young-old (age: 69.26 ± 2.83 years, BMI: 32.0 ± 3.85 kg/m2) and 49 old-old (age: 78.06 ± 2.88 years, BMI: 30.67 ± 3.64 kg/m2). After 12 months of intervention and despite lockdown, the young-old group increased MedDiet adherence (+1 point), but both groups drastically decreased daily PA, especially old-old participants. Fat mass significantly declined in the total population and the young-old. Depression significantly increased (26.9% vs. 21.0%, p < 0.0001), especially in the old-old (36.7% vs. 22.0%, p < 0.0001). No significant changes were found in the glycemic or lipid profile. Conclusions: This study indicates that ongoing MedDiet intake and regular PA can be considered preventative treatment for metabolic diseases in MHOe subjects. However, mental health worsened during the study and should be addressed in elderly individuals.